VD_FINDINFO Plainte / 2013 / 11 vom 8. April 2013 - VD Tribunal cantonal (2013)
ACTION EN CONTESTATION DE L'ÉTAT DE COLLOCATION, PLAINTELP, PRODUCTION DE CRÉANCE, DIVIDENDELP | 18 al. 1 LP, 250 al. 2 LP, 261 LP